Digital Payment - A Dream or Reality for Vietnamese in Rural and Remote Areas? : World Bank Social Protection Payments Assessment for Vietnam - World Bank (World Bank, Washington, DC, 2020)
The World Bank has been supporting the Ministry of Labor, Invalids, and Social Affairs (MOLISA) in their efforts to bring about reforms in the administration and efficient delivery of social security programs. Several countries have been using technological advances in banking as well as telecommunications to digitize and improve welfare delivery programs. Electronic payments have the potential to improve client experience and reduce program costs. Social protection (SP) and social assistance (SA), programs will benefit by moving from current models of cash disbursement to non-cash, direct-to-account electronic payment models. This report provides an assessment of the status of social protection payments in Vietnam, the legal and regulatory framework, and the technical infrastructure for electronic payments and discusses steps towards implementation of digital payment for social protection programs in Vietnam. After assessing payment infrastructure, regulatory framework, and program policies, some significant changes are proposed to enable a transition from cash to non-cash payments. There are also several next steps for MoLISA and VSS to take right away, in addition to actions needed by other key stakeholders.